PRAKTIK POLITIK DALAM SEJARAH ISLAM ERA DINASTI-DINASTI ISLAM - Nurfazillah (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2020)
This article focuses discussion on the political practices of the three great dynastic eras in Islamic history. The purpose of this paper is to describe how political practice during the Islamic dynasties in Islamic history. The problems that want to be answered in this paper is: how political practices in that era were carried out for Umaiyah, Abbasid, and the Turkish Ottoman dynasty. This journal using qualitative-descriptive methods as a literature research. Based on the results of the study it is found that the political practices in these three dynastic eras were not entirely the same. Even though, they were led by a caliph but in case they have different political practices. For example: the Umaiyyah dynasty in the political practice of its government was assisted by diwan. The Abbasid dynasty was guarded by a hajib. There are also wazir and katib as assistants to the caliph in running the wheels of government. And then, the Turkish Ottoman dynasty formed the assembly of syura (mesrevet), mufti and qadhi as his servants.